Enhancing EFL Students’ Vocabulary Mastery Through Taylor Swift’s Song “Opalite”: Students’ Perceptions - Intan Putri Dianti; Cici Situmorang; Melia Melia; Muhammad Ilyas Mahesa (Journal of Innovative and Creativity, 2026)
Vocabulary mastery is essential in English language learning because it significantly influences overall language proficiency. However, vocabulary instruction in EFL classrooms is still frequently dominated by conventional and less contextual approaches, which often cause newly learned vocabulary to be easily forgotten. Therefore, more meaningful and engaging learning media are needed, such as English songs. This study explores EFL students’ perceptions of Taylor Swift’s song Opalite in enhancing vocabulary mastery, particularly noun vocabulary. A descriptive qualitative approach was applied, and the data were obtained through semi-structured interviews. Before the interviews, students participated in learning activities involving the song Opalite accompanied by a lyrics gap-fill activity. The data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that students perceived the song Opalite positively because it presents vocabulary in meaningful contexts, encourages repeated exposure to vocabulary, and facilitates incidental vocabulary acquisition. In addition, song-based learning was considered effective in increasing learning motivation, creating a more enjoyable classroom atmosphere, and providing additional benefits for the development of listening and pronunciation skills. Therefore, songs are a beneficial learning medium for enhancing vocabulary mastery in higher education.